Analysis of three-dimensional curved beams using isogeometric approach. (15th June 2016) - Zhang, Guodong; Alberdi, Ryan; Khandelwal, Kapil
Highlights: Isogeometric approach is presented for finite element analysis of arbitrary curved beams. Both geometry and unknown fields in FEA are interpolated with NURBS. Isogeometric approach allows direct analysis of curved beams generated using CAD. Locking issue is addressed by using higher order NURBS basis functions. Variety of curved beam examples are solved to show the effectiveness of the method. Abstract: There is an increasing trend among architects to utilize curved structural members as opposed to traditional straight structural members in the design of modern space structures. To handle the complex geometrical forms, new structural analysis methods are needed to accurately and efficiently analyze these structures. To address this issue, an isogeometric approach is presented in this paper for the formulation of finite elements for arbitrary spatially curved 3-D beams. These elements employ the same Non-Uniform Rational B-Spline (NURBS) interpolations as used in the CAD representations to interpolate both geometry and unknown fields in the finite element analysis, leading to a seamless transition between complex CAD models utilized by architects and the analysis models used by engineers. The effectiveness of the proposed method is demonstrated on a variety of curved structural geometries of varying complexities.